Improved flotation of artificial galena using a new catanionic mixture. (15th March 2020) - Wang, Zhen; Peng, Yang; Zheng, Yongxing; Ding, Wei; Wang, Jinming; Xu, Longhua
Graphical abstract: Synergistic effect between the components of catanionic mixtures can make up the adverse effect of S vacancy defect on the flotation of AG with single KAX. Highlights: Artificial galena (AG) floats worse than nature galena (NG) with Potassium amylxanthate (KAX). AG flotation recovery with catanionic mixture (CM) near NG with KAX. More near surface S vacancy defects responsible for the worse floatability of AG with KAX. Abstract: Issues related to environmental pollution and resource wastage have made the utilisation of Pb-bearing Zn residue an extremely urgent requirement. The floatability of artificial galena (AG) with a traditional xanthate collector was greatly improved by using a catanionic mixture (CM) as a collector, and the micromechanism was examined using flotation, zeta potential, adsorption, and slow positron beam measurements, together with molecular dynamics simulation. The flotation results revealed that the floatability of AG was inferior to that of natural galena (NG) when potassium amyl xanthate (KAX) was used as the collector, but it improved when using the CM. The results of zeta potential measurements, adsorption experiments, and slow positron beam detection demonstrated that the amount of KAX adsorbed on AG in the KAX/AG system was lower than that on NG in the KAX/NG system because of the greater electronegativity of surface Pb active sites resulting from the presence of S vacancy defects in AG. The molecular dynamics simulation showed that cetyl pyridine chloride and KAX promoted each other's adsorption in the CM/AG system because of the electrostatic attraction between the sulfhydryl and pyridyl groups and the hydrophobic attraction between the amyl and cetyl groups. An adsorption model was proposed to better explain the greater floatability of AG when using the CM.